Access to healthcare for people with disabilities in South Africa: Bad at any time, worse during COVID-19? - Emma L. McKinney; Victor McKinney; Leslie Swartz (South African Family Practice)
People with disabilities, especially those living in low- and middle-income countries, experience significant challenges in accessing healthcare services and support. At times of disasters and emergencies, people with disabilities are further marginalised and excluded. During the coronavirus disease 2019 (COVID-19) pandemic, many people with disabilities are unable to access healthcare facilities, receive therapeutic interventions or rehabilitation, or gain access to medication. Of those who are able to access facilities, many experience challenges, and at times direct discrimination, accessing life-saving treatment such as intensive care unit admission and ventilator support. In addition, research has shown that people with disabilities are at higher risk of contracting the virus because of factors that include the need for interpersonal caregivers and living in residential facilities. We explore some of the challenges that people with disabilities residing in South Africa currently experience in relation to accessing healthcare facilities.